Seismic Safety Evaluation of Mechanically Stabilized Earth (MSE) Wall for Highway Construction - Rizali, Muhammad Adi Ibrahim; Yusep Muslih Purwana (Himpunan Ahli Teknik Tanah Indonesia, 2024)
The usage of Mechanically Stabilized Earth (MSE) Walls has grown in popularity over the last few decades and has been widely used in many countries for highway construction, including Indonesia. As a country with a high risk against seismic hazards, a considerable stability analysis against earthquakes for construction must be conducted. This paper is directed to evaluate the static and seismic stability of MSE wall by adopting design criteria from SNI 8460:2017 using the pseudo-static approach with Limit Equilibrium Method (LEM) which modelling earthquake as a seismic coefficient, a one-way constant load and dynamic response approach with Finite Element Method (FEM) which modelling earthquake as ground motion, a fluctuating load which varies in time. The stability analysis is performed by considering three failure mechanisms that mostly occurred in MSE Walls; base sliding, tensile overstress, and slope failure. The earthquake load is modelled based 1000-year return period earthquake. Based on the analysis result, the most potential failure mechanism that may occur in the MSE wall is tensile overstress, while the least potential failure is base sliding. The analysis result also shows that the finite element method obtained higher safety factors compared to limit equilibrium, while on the other hand, the remaining two failure mechanisms shows the different result, with the finite element method obtaining lower safety factors than limit equilibrium. Modelling seismic load as an accelerogram indicates that earthquakes have higher impacts on structure stability compared to seismic coefficient, based on seismic safety factor reduction of each method. Although show differences in the value of the safety factor, the minimum safety factor required still complies with both methods.